Gastric adenocarcinoma with choriocarcinoma component - Aliaga, Rolig (2020)
A 48 year-old patient with abdominal pain associated and weight loss is shown. Endoscopy shows an ulcerated, friable, circumferential infiltratory lesion that compromises the pyloric canal and duodenal bulb The histopathological study reveals intestinal type adenocarcinoma with area of differentiation in coriocarcinoma. A partial distal gastrectomy and subsequent chemotherapy were performed aimed at the lineage of the coriocarcinoma, with good clinical response to the first course.